Metabolic engineering of Saccharomyces cerevisiae for ethanol and butanol biofuel production - Khan, Salman; Hussain, Asif; Hussain, Muhammad Iftikhar; Aqeel, Sahibzada Muhammad; Basharat, Samra; Hussain, Arif; Al-Ansi, Waleed; Abdulqader, Abdulqader; Yao, Nie (International Journal of Environment, Agriculture and Biotechnology, 2023)
The production of biofuels through biological processes has garnered increasing attention due to their potential benefits over conventional fuels, including lower greenhouse gas emissions, higher energy output, and reduced-price fluctuations. However, the metabolic processes of primitive microorganisms used in biofuel production are not compatible with those of fossil fuels. To address this, scholars have employed metabolic engineering techniques to modify the metabolisms of various microorganisms, including S. cerevisiae, for enhanced biofuel production. Specifically, overexpression of enzymes involved in bioethanol and biobutanol production, knockouts of competing pathways, improvements in carbon flux and tolerance have been applied to maximize the potential of S. cerevisiae for bioethanol and biobutanol production. This review focuses on the current state of metabolic engineering of S. cerevisiae for the production of bioethanol from lignocellulose and biobutanol from all kind of substrates, along with the potential use of cell surface technology in this field.